Catalyzing Development : A New Vision for Aid - Jung, Woojin; Makino, Koji; Kharas, Homi J., 1954- (Book collections on Project MUSE., 2011)
"Provides analysis of how the field of international aid is changing with new approaches necessary because of new actors providing assistance, including middle-income countries, private philanthropists, and the private sector, and new challenges, including climate change and the large number of fragile states"--Provided by publisher.